(906) Solution of Variational Problems with Bounded Control Variables حل المشكلات المتنوعة ذات المتغيرات المحدودة التحكم - Salah El-Gendi.; Ahmed Hassan.. (INP, 2024)
The problem can be reduced to the numerical solution of two-point boundary problem for which a new procedure is A simple illustration for the numerical solution of point boundary problems is given and the results compare favorably with other known methods. The variational problems with bounded control variables may also be reduced to a linear programming problem for which standard methods are available.